EFFECTS OF FUKUZAWA YUKICHI’S EDUCATIONAL IDEOLOGIES ON IDEOLOGICAL CHANGES OF PHAN BOI CHAU - Nhan, Duong (IJRDO- Journal of Educational Research, 2018)
Fukuzawa Yukichi (1835 - 1901), a Japanese radical ideologist in the late 19th century, was a pioneer of the education modernization in Japan.  His educational ideologies were not limited in Japanese territory but went beyond Japanese border. Together with New Books (Tân Thư), New Literature (Tân Văn), Fukuzawa Yukichi’s educational ideologies were introduced to Vietnam and they created ideological changes in Confucian scholars, particularly Phan Boi Chau, during the early years of the twentieth century. Phan Boi Chau realized that the only way to independence was to improve intellectual level of the people and strengthen national potentials. The ideological changes of Phan Boi Chau created uniqueness in the history of ideological flow in Vietnam, contributing to the struggle for national liberation.